Predict the Laser Power and Recovery Period in Treatment by Endovenous Laser Ablation (EVLA) - Bushra Ghali Yousif; Sahib Neamah Abdul-Wahid; Kadhum Jawad Shabaa (مجلة بغداد للعلوم)
Eight patients (3 male and 5 female) were treated in this study by Endovenous Laser Ablation (EVLA); Mathematical models are proposed to estimate the applied laser power and to assess the recovery period. The estimations of the applied laser power and recovery period in these models will be depended mainly on the diameter of the incompetent vein.  In addition, Excel Program was utilized to find the proposed models.  A 1470 nm diode laser up to 15W continuous power (CW) was used in the treatment of venous ulcers by EVLA procedure. Following up by duplex ultrasound was started in the 1st week after the first session until the vein is completely closed. The present study concluded that the relationship both between the applied laser power and recovery period with diameter is directly linear. The mathematical results obtained from the two mathematical proposals are consistent with the clinical results